2004
DOI: 10.1152/jn.00262.2004
|View full text |Cite
|
Sign up to set email alerts
|

Response Properties of Whisker-Related Neurons in Rat Second Somatosensory Cortex

Abstract: Kwegyir-Afful, Ernest E. and Asaf Keller. Response properties of whisker-related neurons in rat second somatosensory cortex. J Neurophysiol 92: 2083-2092. First published May 26, 2004 10.1152/jn.00262.2004. In addition to a primary somatosensory cortex (SI), the cerebral cortex of all mammals contains a second somatosensory area (SII); however, the functions of SII are largely unknown. Our aim was to explore the functions of SII by comparing response properties of whisker-related neurons in this area with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 57 publications
4
56
2
Order By: Relevance
“…The distance between VPL neurons and their S2 destination is shorter than the path taken by VPL-S1 axons. Our result is consistent with several previous studies (Woolsey and Wang, 1945;Heppelmann et al, 2001;Kwegyir-Afful and Keller, 2004), which showed that S1 and S2 neurons responded to peripheral stimulation with similar peak latencies in rabbits and rats. However, Brett-Green et al (2003, 2004 and Benison et al (2007) examined epipial-evoked potentials when stimulating a rat's whisker and other body regions, and found a much longer latency of evoked response in S2 than in S1.…”
Section: Thalamic Coactivation Of S1 and S2supporting
confidence: 94%
See 2 more Smart Citations
“…The distance between VPL neurons and their S2 destination is shorter than the path taken by VPL-S1 axons. Our result is consistent with several previous studies (Woolsey and Wang, 1945;Heppelmann et al, 2001;Kwegyir-Afful and Keller, 2004), which showed that S1 and S2 neurons responded to peripheral stimulation with similar peak latencies in rabbits and rats. However, Brett-Green et al (2003, 2004 and Benison et al (2007) examined epipial-evoked potentials when stimulating a rat's whisker and other body regions, and found a much longer latency of evoked response in S2 than in S1.…”
Section: Thalamic Coactivation Of S1 and S2supporting
confidence: 94%
“…In the higher-primates, S2 lost the direct thalamic afferents and depend on the corticocortical inputs from ipsilateral S1 for activation. Summing the various aforementioned studies, results favoring serial transmission were performed mostly on macaque and rhesus monkeys (Pons et al, 1987(Pons et al, , 1988(Pons et al, , 1992Burton et al, 1990), while investigations supporting the parallel view used nonprimitive primates and other mammals, including rats, cats, marmoset monkeys, tree shrews, and opossums (Spreafico et al, 1981;Fisher et al, 1983;Murray et al, 1992;Turman et al, 1995;Coleman et al, 1999;Heppelmann et al, 2001;Zhang et al, 2001a,b;Kwegyir-Afful and Keller, 2004). Our results from rats further support the distinction between serial somatosensory processing in higher primates and parallel somatosensory processing in other mammals.…”
Section: Hierarchical View Of Somatosensory Flowsupporting
confidence: 76%
See 1 more Smart Citation
“…In rats, independent inputs to SI and SII were described with anatomical and electrophysiological techniques (Kwegyir-Afful and Keller, 2004), and a direct parallel pathway to SII from VPL was demonstrated (Liao and Yen, 2008). A recent study in mice using flavoprotein autofluorescence imaging in brain slices (Theyel et al, 2010), combined with anatomical and electrophysiological experiments confirmed it.…”
Section: Discussionmentioning
confidence: 92%
“…Typically, analysis of angular tuning has been performed only on responses to deflections of the principal vibrissae, which evoke the largest magnitude responses in their associated neurons. However, many vibrissae in a receptive field may evoke spikes, and in some brain regions, these adjacent (nonprincipal) vibrissae can evoke response magnitudes similar to those evoked by the principal vibrissa (principal trigeminal nucleus: Veinante and Deschênes 1999;thalamus: Diamond et al 1992; primary somatosensory cortex: Bruno and Simons 2002; second somatosensory cortex: Kwegyir-Afful and Keller 2004;superior colliculus: Hemelt and Keller 2007). This raises the question whether the angular tuning of the principal vibrissa is preserved across the receptive field, that is, if nonprincipal vibrissae within a receptive field respond with similar angular tuning to those produced by the principal vibrissa.…”
Section: Introductionmentioning
confidence: 99%